Variables in the relationship between Iraq and the United States in light of the challenges of terrorism and the violation of sovereignty - Saeedi , Osama Al- Saeedi; Al-Sahaf , Muhammad Nimah (The International and Political Journal, 2025)
This research aims to analyze the nature of the variables that have influenced the course of the relationship between Iraq and the United States, in light of the security and political challenges Iraq has faced since 2003—particularly those related to terrorism and the violation of sovereignty. The study focuses on examining the key turning points in this relationship, beginning with the U.S. occupation of Iraq, followed by the withdrawal phase, and then the military return under the umbrella of the international coalition against ISIS, with a special emphasis on the legal and political dimensions of the relationship. The research adopts both descriptive and analytical approaches to deconstruct internal and external influencing factors. It concludes that the future of Iraq–U.S. relations depends on Iraq's ability to assert its sovereign decision-making and to rebuild its security and political institutions in a manner that ensures balance in its international relations. The study finds that the relationship between Iraq and the United States has undergone significant fluctuations since 2003. Washington played a central role in toppling the former regime and rebuilding the Iraqi state. However, the relationship has been impacted by major challenges, most notably the rise of terrorism and the repeated violations of Iraq’s sovereignty by the United States through military interventions and political pressure.